Historical and current predictors of self-reported health status among elderly persons in Barbados - Hambleton, Ian R.; Clarke, Kadene; Broome, Hedy L.; Fraser, Henry S.; Brathwaite, Farley; Hennis, Anselm J. (Revista panamericana de salud pública, 2005)
To understand the relative contribution of past events and of current experiences as determinants of health status among the elderly in the Caribbean nation of Barbados, in order to help develop timely public health interventions for that population. The information for this prevalence study was collected in Barbados between December 1999 and June 2000 as part of the "SABE project," a multicenter survey in seven urban areas of Latin America and the Caribbean that evaluated determinants of health and well-being in elderly populations (persons 60 and older). We used ordinal logistic regression to model determinants of self-reported health status, and we assessed the relative contribution of historical socioeconomic indicators and of three current modifiable predictor groups (current socioeconomic indicators, lifestyle risk factors, and disease indicators), using simple measures of association and model fit. Historical determinants of health status accounted for 5.2% of the variation in reported health status, and this was reduced to 2.0% when mediating current experiences were considered. Current socioeconomic indicators accounted for 4.1% of the variation in reported health status, lifestyle risk factors for 7.1%, and current disease indicators for 33.5%. Past socioeconomic experience influenced self-reported health status in elderly Barbadians. Over half of this influence from past events was mediated through current socioeconomic, lifestyle, and disease experiences. Caring for the sick and reducing lifestyle risk factors should be important considerations in the support of the current elderly. In addition, ongoing programs for poverty reduction and increased access to health care and education should be considered as long-term strategies to improve the health of the future elderly.